Determination of priority criteria in green building transformation: An analysis on the service industry - Serkan Eti; Hasan Dinçer; Serhat Yüksel; Yeter Demir Uslu; Yaşar Gökalp; Hakan Kalkavan; Alexey Mikhaylov; Gabor Pinter (Research in Globalization, 2023)
The purpose of this study is to identify priority criteria in green (net zero energy) building transformation. For this purpose, an analysis has been conducted for hospitals by considering new methodology. In this scope, firstly, 10 different indicators are selected with the help of literature examination. After that, by using this new methodology, the weights of these items are computed. The main contribution of this study is that a priority evaluation is conducted so that more critical indicators of green building transformations can be identified. Because of this issue, for financial sustainability, companies should firstly focus on more significant factors. Another important novelty of this study is that a new decision-making technique is generated. With the help of this issue, both problems in methodology can be solved and methodological originality can be achieved. The findings show that renewable energy usage is the most critical factor.
Keywords: 330; Carbon Emission; Clean Energy; Fuzzy Decision-Making; Green Building; Healthcare Industry